Etyka i pamięć o Zagładzie - Liszka, Katarzyna (Nowa Humanistyka, 2016)
In her book, Katarzyna Liszka provides the reader with a clearly outlined map of the main sides of the debate on the 'division of labour of memory' after the Holocaust, examines the arguments, which are used in this dispute, together with an analysis of ethical implications, which, according to the author, have a fundamental significance for the majority of Jewish thinkers taking a stance in this debate. This angle, with the focus on the plural 'ethics of memory' in the beginning of the work, allows the author to connect various idioms of philosophy, theology and sociology of the twentieth century, as complementary elements of reflection framed as a way of remembering. In this perspective, the subsequent notional mediations, corrections of approaches taken by Hannah Arendt, Avishai Margalit, or Zygmunt Bauman, become an indirect proof of the crystallisation, not only of the aforementioned community of memory work, but also of the transformation of ethical and legal categories related to the issue of the community of universal ethics, which the author writes about in the conclusion of her work, with reference to the reflections of Natan Sznaider and Daniel Levi. (excerpt from a review by Dr hab. Tomasz Majewski)